ANALYSIS OF SPEED AND TRAFFIC DENSITY OF JALAN RAJAGALUH - MAJALENGKA - M. Nanda Fajar Arij Rachman; Indrastuti (Fakultas Teknik Sipil dan Perencanaan, 2024)
Concerns about the density of roads and acceleration have been brought up globally by the increase in motorized vehicles, especially in urban areas where infrastructure development is still in progress. The issues of road density and congestion are the main focus of this study, with a particular concentration on road speeds on Pangeran Muhammad's road, which leads to Cirebon Street in Rajagaluh, about 100 meters away. This study's principal goal is to ascertain the average speed and vehicle density on the road by applying qualitative research techniques and on-the-ground observations. We looked at the volume of traffic, the passing velocity, and the density of the road. to gather primary data. The quantity of automobile traversing was ascertained using Traffic Counter software and Microsoft Excel 2021.; MKJI 1997 provided secondary data. In street data analysis involving two-way double-track (2/2 UD), cut line road markings designate the column separator, and each column has a width of ± 3.5 meters. The traffic and congestion on the road under review are reflected in the density data. Monitoring and evaluating these parameters is required to obtain data regarding traffic density and road performance in the area under study. The data indicates that most vehicles crossed the reviewed street between 4 and 5 p.m., when the highest vehicle volume occurred, with a peak of 2505.6 vehicles per hour (Smp/Hour). Additionally, observations show that on Sunday, between 11 a.m. and 12 p.m., when traffic is smoother, vehicles reach their average peak speed of 50.51 km/h, allowing for relatively high speeds.